KONSEP PENDIDIKAN TAUHID DALAM PEMIKIRAN HASAN AL-BANNA DAN KH. HASYIM ASY’ARI : RELEVANSI TERHADAP PEMBENTUKAN KARAKTER MUSLIM DI ERA MODERN - Wahyudi Mutalib; Ahmad Mujahidin; Mohammad Nahrawi; Ahsan Hakim (Educational Research Center, 2025)
This study aims to analyze and compare the concept of tauhid education in the thoughts of Hasan Al-Banna and KH. Hasyim Asy‘ari, as well as its relevance to the formation of Muslim character in the modern era. The background of this research is rooted in the spiritual and moral crisis that accompanies technological advancement and globalization, which demands a reorientation of Islamic education based on tauhid values. This research employs a library research approach using content analysis methods on the major works of both figures, such as Majmū‘at al-Rasā’il and Adāb al-‘Ālim wa al-Muta‘allim. The analysis reveals that Hasan Al-Banna emphasizes tauhid education as an integral system that cultivates divine consciousness, shapes the personality of da‘wah activists, and builds Islamic civilization. Meanwhile, KH. Hasyim Asy‘ari highlights the spiritual dimension, adab (ethics), and the exemplary role of scholars (‘ulama’) as the foundation for forming a noble Muslim character. Both figures share the paradigm that tauhid is not merely a theological doctrine but also an epistemological and axiological principle of education. The findings contribute to developing a tauhid-based character education model that is contextual and applicable in facing the challenges of modernity. Theoretically, this study enriches the treasury of Islamic educational philosophy, while practically, it serves as a reference for developing a holistic Islamic character curriculum.